Elasto-plastic stability of thin plates subjected to complex loading process - Bich, Dao Huy (Vietnam Journal of Mechanics, 1994)
Analyzing an elastic-plastic stability problem, the complex loading process acted on the body has an essential influence on the values of critical loads. For clearing up this effect, in the present paper the general elasto-plastic process theory, theory of process with average curvature and the simple loading process theory are applied into the consideration of the mentioned problem. A numerical comparison is given.